Defensive Medicine in Neurosurgery: Does State-Level Liability Risk Matter?. Issue 2 (February 2015) - Smith, Timothy R.; Habib, Ali; Rosenow, Joshua M.; Nahed, Brian V.; Babu, Maya A.; Cybulski, George; Fessler, Richard; Batjer, H. Hunt; Heary, Robert F.
Abstract : BACKGROUND: Defensive medicine is prevalent among US neurosurgeons due to the high risk of malpractice claims. This study provides national estimates of US neurosurgeons' defensive behaviors and perceptions. OBJECTIVE: To examine the relationship of defensive medicine—both "assurance" behaviors and "avoidance" behaviors—to the liability environment. METHODS: A 51-question online survey was sent to 3344 US neurosurgeon members of the American Board of Neurological Surgeons (ABNS). The survey was anonymous and conducted over 6 weeks in the spring of 2011. The previously validated questionnaire contained questions on neurosurgeon, patient, and practice characteristics; perceptions of the liability environment; and defensive-medicine behaviors. Bivariate and multivariate analyses examined the state liability risk environment as a predictor of a neurosurgeon's likelihood of practicing defensive medicine. RESULTS: A total of 1026 neurosurgeons completed the survey (31% response rate). Neurosurgeons' perceptions of their state's liability environment generally corresponded well to more objective measures of state-level liability risk because 83% of respondents correctly identified that they were practicing in a high-risk environment. When controlling for surgeon experience, income, high-risk patient load, liability history, and type of patient insurance, neurosurgeons were 50% more likely to practice defensive medicine in high-risk states compared with low-risk-risk states (odds ratio: 1.5, P < .05). CONCLUSION: Both avoidance and assurance behaviors are prevalent among US neurosurgeons and are correlated with subjective and objective measures of state-level liability risk. Defensive medicine practices do not align with patient-centered care and may contribute to increased inefficiency in an already taxed health care system.